Ecological validity of a deep learning algorithm to detect gait events from real-life walking bouts in mobility-limiting diseases - Romijnders, Robbin; Salis, Francesca; Hansen, Clint; Küderle, Arne; Paraschiv-Ionescu, Anisoara; Cereatti, Andrea; Alcock, Lisa; Aminian, Kamiar; Becker, Clemens; Bertuletti, Stefano; Bonci, Tecla; Brown, Philip; et al. (Frontiers in Neurology, 2023)
Clinical assessment of mobility, and walking specifically, is still mainly based on functional tests that lack ecological validity. Thanks to inertial measurement units (IMUs), gait analysis is shifting to unsupervised monitoring in naturalistic and unconstrained settings. However, extraction of clinically relevant gait parameters from IMU data often depends on heuristics-based algorithms that rely on empirically determined thresholds. These were mainly validated on small cohorts in supervised settings. Here, a deep learning (DL) algorithm was developed and validated for gait events detection in a heterogeneous population of different mobility-limiting disease cohorts and a cohort of healthy adults. Participants wore pressure insoles and IMUs on both feet for 2.5 hours in their habitual environment. The raw accelerometer and gyroscope data from both feet were used as input to a deep convolutional neural network, while reference timings for gait events were based on the combined IMU and pressure insoles data. The results show a high detection performance for initial contacts (ICs) (recall: 98%, precision: 96%) and final contacts (FCs) (recall: 99%, precision: 94%), and a maximum median time error of −0.02 s for ICs and 0.03 s for FCs. Subsequently derived temporal gait parameters were in good agreement with a pressure insoles-based reference with a maximum mean difference of 0.07 s, −0.07 s and <0.01 s for stance, swing, and stride time, respectively. Thus, the DL algorithm is considered successful in detecting gait events in ecologically valid environments across different mobility-limiting diseases.